2005 IEEE/RSJ International Conference on Intelligent Robots and Systems 2005
DOI: 10.1109/iros.2005.1545303
|View full text |Cite
|
Sign up to set email alerts
|

Designing robots for long-term social interaction

Abstract: Abstract-Valerie the Roboceptionist is the most recent addition to Carnegie Mellon's Social Robots Project. A permanent installation in the entranceway to Newell-Simon Hall, the robot combines useful functionality-giving directions, looking up weather forecasts, etc.-with an interesting and compelling character. We are using Valerie to investigate human-robot social interaction, especially long-term human-robot "relationships." Over a nine-month period, we have found that many visitors continue to interact wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
207
1
8

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(227 citation statements)
references
References 11 publications
(9 reference statements)
2
207
1
8
Order By: Relevance
“…Results from a first study [13] indicated that, after a certain period, only few users interacted with the robot for more than 30 seconds. To avoid this, the authors proposed some design recommendations such as proper greeting and farewell behaviors, more interactive dialogue or a robust way of identifying repeated visitors.…”
Section: Introductionmentioning
confidence: 99%
“…Results from a first study [13] indicated that, after a certain period, only few users interacted with the robot for more than 30 seconds. To avoid this, the authors proposed some design recommendations such as proper greeting and farewell behaviors, more interactive dialogue or a robust way of identifying repeated visitors.…”
Section: Introductionmentioning
confidence: 99%
“…Recent years have seen impressive advances in the mechanical aspects of this problem, yet progress on social interaction has been slower (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Research suggests that low-level information, such as animacy, contingency, and visual appearance, can trigger powerful social behaviors toward robots during the first few minutes of interaction (16,17).…”
mentioning
confidence: 99%
“…For instance, we have robots that lead tours in museums (Burgard et al, 1998), robots that act as receptionists (Gockley et al, 2005), and robots that function as pets (Fujita, 2001). As robots begin to occupy roles traditionally reserved for people, the need for robots that are able to interact in a complex manner with human beings has increased dramatically.…”
Section: Motivationmentioning
confidence: 99%